PDGFRA mRNA is overexpressed in oral cancer patients as compared to normal subjects with a significant trend of overexpression among tobacco users - Ong, Hui Shan; Gokavarapu, Sandhya; Tian, Zhen; Li, Jiang; Xu, Qin; Cao, Wei; Zhang, Chen Ping (Journal of oral pathology & medicine, 2017)
Background Platelet‐derived growth factors alpha (PDGFA) is a tyrosine kinase receptor activator which is known to be amplified in the malignancies, and their expression levels are correlated to tumor progression and reduced overall survival. The expression of PDGFRA is different among the tumors and normal tissues; furthermore, their expression level is site specific. Under a physiological condition, PDGFRA and its ligand are expressed in distinct cell populations and activated in a paracrine manner. Nevertheless, heterodimer characteristic of PDGFRA allows it to be trans‐activated by non‐specific ligands or via autocrine manner. The future of cancer therapy can be based on PDGFRA receptor blockade and therefore warrants further investigation to determine the differing expression of PDGFRA between controls and patients with oral squamous cell carcinoma (OSCC). Methods We performed a case‐control study of 111 patients with newly diagnosed tongue squamous cell carcinoma and 111 control subjects without a cancer diagnosis, matched for age and gender, to evaluate the association between PDGFRA expression levels in oral mucosa. We then performed smoking stratification in each cohort. Independent t test analysis was applied for case‐control comparisons. Results Mean value of PDGFRA mRNA level (−ΔCt) for normal cohort is −30.242, whereas mean value of PDGFRA mRNA level for patients with OSCC is −11.516. PDGFRA mRNA level (−ΔCt) was significantly higher in oral cancer cohort, P<.001. Smokers have a significantly higher PDGFRA mRNA expression in comparison with non‐smokers (P=.002) among the non‐cancer group. Likewise, this trend is observed in cancer cohort too, P=.044. Conclusion PDGFRA expression is significantly higher in oral cancer cohort with or without the establishment of tobacco risk factor.